If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(9x+12)=3x+5
We move all terms to the left:
1/3(9x+12)-(3x+5)=0
Domain of the equation: 3(9x+12)!=0We get rid of parentheses
x∈R
1/3(9x+12)-3x-5=0
We multiply all the terms by the denominator
-3x*3(9x+12)-5*3(9x+12)+1=0
Wy multiply elements
-9x^2(9-15x(9+1=0
| (y/y+5)=(-5/y+5)+(5/4) | | 2q+432=856 | | h-64=54 | | -(3m+8)=5m-8 | | -2+w=-7 | | 1/2(2a+3)-4a-8)=7 | | 5k-9/5=-2 | | 112=6x-4 | | 3,486=40(p+42) | | 11x/24-11=x/6+10 | | -2x-(-3x)=6 | | 91=-105–h | | 9(2)+2y=72 | | 6y=4y* | | -21+3x=-33 | | M=-1/2t^2+5/2t | | n/7+6=8 | | 3(8-6)=-5a-(7+3a) | | 8x+4=2(4x-2) | | 1/2(8x+26)=4x+13 | | -133=-63–-7c | | 1.25x-6.75=31.75 | | 11/3xY=31/2 | | 3x-5(x-2)=-3+2x-11 | | -4f=6−6f | | 3(4+5y)=15 | | 3j=4j+5 | | 3/11=6/y | | 10x-2+1x+4=120 | | 31.75-6.75=1.25x | | 3q=8+q | | 3x-5(x-2)=-3-2x+11 |